Coronavirus: impact on the economy and financial markets - E. A. Barinov (Путеводитель предпринимателя, 2020)
The article examines the impact of the pandemic on the world economy. The impact of the OPEC+ oil agreement and the reduction of its production on financial markets and exchange rates is noted. Data are provided on the losses of a number of countries from the decline in prices for this energy carrier and the increase in the incidence of coronavirus infection in the population. The article analyzes the measures taken by Western countries and Russia to help national companies and populations affected by the pandemic.